Religious Moderation as a Model for Character Education in Indonesia: A Case Study of Al-Fattah Islamic Elementary School in Sarolangun, Jambi - Suparno; Abdul Ramae Sulong; Ansori; Fahrizal; Muhamad Taridi (Islam Transformatif : Journal of Islamic Studies, 2025)
Abstract This study investigates the implementation of religious moderation as a core strategy for character education at SDI Al-Fattah Payolebar, addressing growing concerns about declining students’ discipline and moral values. Grounded in Thomas Lickona’s theory of character education, this research offers a novel perspective by integrating daily spiritual routines, such as congregational prayers, Qur’anic recitation, and dhikr, with active teacher supervision and family involvement. Employing a qualitative-descriptive method with a case study design, and thematic analysis, data were collected through observation, interviews, and document analysis. The findings reveal that structured religious practices, when consistently reinforced by teachers and supported within the family environment, contribute significantly to the development of key moral traits, including religiosity, empathy, responsibility, and self-discipline. However, several challenges persist, particularly parental disengagement and inconsistencies in students’ behavioral internalization of these values. Theoretically, this study contributes to the discourse on moral education within Islamic educational. Practically, It offers a contextual model that may be adapted by similar educational institutions. the study concludes that collaboratively implemented religious habituation constitutes an effective approach to fostering holistic character development among students.   Abstrak Penelitian ini mengkaji implementasi moderasi keagamaan sebagai strategi utama dalam pendidikan karakter di SDI Al-Fattah Payolebar, sebagai respons atas kekhawatiran terhadap menurunnya disiplin dan nilai-nilai moral siswa. Berlandaskan teori pendidikan karakter Thomas Lickona, riset ini menawarkan perspektif baru dengan mengintegrasikan rutinitas spiritual harian—seperti salat berjemaah, tilawah al-Qur’an, dan zikir—dengan pengawasan guru yang aktif serta keterlibatan keluarga. Dengan pendekatan kualitatif-deskriptif, desain studi kasus, dan analisis tematik. Data dikumpulkan melalui observasi, wawancara, dan analisis dokumen. Hasil penelitian menunjukkan bahwa praktik keagamaan yang terstruktur dan dijalankan secara konsisten, apabila diperkuat oleh guru dan didukung oleh orang tua, mampu menumbuhkan nilai-nilai religius, empati, tanggung jawab, dan kedisiplinan pada siswa. Namun demikian, beberapa tantangan tetap ada, terutama terkait rendahnya keterlibatan orang tua dan perilaku siswa yang tidak konsisten. Secara teoretis, studi ini memperluas wacana mengenai pendidikan karakter berbasis nilai-nilai Islam dan secara praktis menawarkan model yang dapat diadaptasi oleh institusi pendidikan serupa. Kesimpulannya, pembiasaan keagamaan yang dijalankan secara kolaboratif merupakan instrumen yang efektif dalam membentuk karakter siswa secara holistik.